2022
DOI: 10.3390/ijms23094742
|View full text |Cite
|
Sign up to set email alerts
|

Plant Kunitz Inhibitors and Their Interaction with Proteases: Current and Potential Pharmacological Targets

Abstract: The action of proteases can be controlled by several mechanisms, including regulation through gene expression; post-translational modifications, such as glycosylation; zymogen activation; targeting specific compartments, such as lysosomes and mitochondria; and blocking proteolysis using endogenous inhibitors. Protease inhibitors are important molecules to be explored for the control of proteolytic processes in organisms because of their ability to act on several proteases. In this context, plants synthesize nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 103 publications
0
23
0
6
Order By: Relevance
“…Previous studies have reported that C. dioscoridis extract exhibits antioxidant, antiinflammatory, anti-nociceptive, anti-hyperglycemic, and anti-diabetic activity [15][16][17][18][19]. Interestingly, several studies demonstrated the anticancer activity of the bioactive components and the crude extract of C.dioscoridis [20][21][22][23][24][25]. Several protease inhibitors from C.dioscoridis have been purified and characterized.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported that C. dioscoridis extract exhibits antioxidant, antiinflammatory, anti-nociceptive, anti-hyperglycemic, and anti-diabetic activity [15][16][17][18][19]. Interestingly, several studies demonstrated the anticancer activity of the bioactive components and the crude extract of C.dioscoridis [20][21][22][23][24][25]. Several protease inhibitors from C.dioscoridis have been purified and characterized.…”
Section: Introductionmentioning
confidence: 99%
“…These protease inhibitors showed cytotoxic activity equal to the crude extract. They have been identified as potential antitumor targets because of their involvement in proteostasis [24,25]. Recently, El-Gamal et al (2021) confirmed that C.dioscoridis extract has anticancer and anti-aging activities as it showed significant inhibitory activity against hyaluronidase collagenase, tyrosinase and elastase [22].…”
Section: Introductionmentioning
confidence: 99%
“…Genetic manipulation of plants also remains highly inefficient, without a routinely successful, genotype independent transformation protocol, and further insights onto the hurdles facing direct or indirect recombinant DNA technology, as well as its genetic, molecular, and regulatory element requirements are thoroughly discussed in a review by Basso et al (2020). For purposes of efficiently establishing new beneficial and widely functional protease inhibitors such as recombinant serine protease inhibitors (rBbKI), serine and cysteine inhibitors (rBbCI) derived from native inhibitors discovered from Bauhinia bauhinioides seeds, as well as serine and metalloprotease inhibitors from Enterolobium contortisiliquum seeds, more knowledge of their structure, selectivity and specificity to the different peptidase enzymes, including their target enzyme activity, must be gathered (Ferreira et al, 2019;Bonturi et al, 2022).…”
Section: Target Protein Inhibitory Mechanism Engineered Crop Referencesmentioning
confidence: 99%
“…Additionally, protease inhibitors also exhibit direct interfering effects on endogenous proteases altering the physiological or compositional characteristics of the transgenic host plant. In this case, RPIs could rapidly interfere with the regulation of several metabolic processes such as the elimination of misfolded proteins, polypeptide pre-and pros-region processing during protein maturation and turnover of certain essential proteins (Solomon et al, 1999;Buono et al, 2019;Bonturi et al, 2022).…”
Section: Biochemical and Physiological Effectsmentioning
confidence: 99%
See 1 more Smart Citation